The New Testament Gospels and the Gospel of Thomas: A New Direction - Wood, John Halsey (New Testament studies, 2005)
After surveying the debate over the relation of the Gospel of Thomas to the NT gospels, this essay argues that Gos. Thom. merits comparison with second-century Christian literature, in order to discern the similarity or dissimilarity with regard to the use of NT material. The second-century sources considered are found to manifest various types of literary dependence on the canonical gospels. A comparison suggests that Gos. Thom. does show many of the characteristics of this Christian literature known to depend on NT material, and, moreover, that Gos. Thom. appears to draw from all four of the canonical gospels. In fact, the significance of Gos. Thom. may not be as a witness to the historical Jesus, as some have hoped, but as one of the earliest witnesses to a four-gospel collection.